EVALUASI KURIKULUM METODOLOGI PEMBELAJARAN PAI PADA PRODI PAI UNISNU JEPARA - Fathur Rohman (Universitas Islam Nahdlatul Ulama Jepara, 2015)
Learning methodology PAI at UNISNU Jepara as the one of subject for students ability to understand how to implement learning methodology in class. However, in term of substance, curriculum of the subject is considered not entirely relevant to the required competences. While, from the balance aspect, competence which is so vast is not supported by the vast curiculum content as well.Therefore, the writer wants to evaluate the curriculum learning methodology PAI, both of substance aspect and the curiculum content. The problem of the research is focused on the study of the subtance and the content of learning methodology PAI at UNISNU Jepara, as well as the relevance of the two aspects. The research method used is a case study. The data collection is triangulation. While, the analysis used a qualitative descriptive technique with content analysis approach.The result of the research indicate that there is a discrepancy between learning methodology PAI substance and formulated standard competence. On the other hand, standard competence are not quite complete because it only includes cognitive domains. While, in this curriculum content is consist of several irrelevant materials to the subtance of the subject.Therefore, the writer tried to redesign curriculum of the subject to redefine subtance and standard competency